Locally generated C3 regulates the clearance of Toxoplasma gondii by IFN-γ-primed macrophage through regulation of xenophagy - Liu, Bo; Yan, Yan; Wang, Xiaoreng; Chen, Nannan; Wu, Jue (Frontiers in Microbiology, 2022)
Exogenous pathogen infection can induce autophagy in cells. Autophagy is essential for cell survival, development and homeostasis. It not only regulates cell defense and stress, but also has a close relationship with innate and adaptive immunity. Complement is an important part of innate immunity, which could be activated by three approaches, including classic, alternative and lectin pathways. All the three pathways result in the activation of C3, and generate anaphylatoxins fragments C3a and C5a, and formation of the membrane attack complex. Either C3a or C5a induce the inflammatory cytokines through binding to C3aR or C5aR, respectively. However, it is still unknown whether the complement could regulate the autophagy of intracellular microorganisms or not. In this study, we constructed a Toxoplasma gondii (T. gondii) and macrophages co-culture experimental model using T. gondii expressing enhanced green fluorescence protein (EGFP) fluorescence and C3-/-C57BL/6J mice for that T. gondii invaded peritoneal macrophages in mice. Western blot, laser confocal microscopy (LCM) and transmission electron microscopy (Lewis et al.) were used to observe the changes of autophagy between the macrophages from wild type (WT) and C3-/- mice. Flow cytometry and LCM were used to investigate the effect of autophagy on the killing ability of macrophages against T. gondii. Here, we found that local C3 could suppress not only the canonical autophagy of macrophage, but also the xenophagy to T. gondii. Interestingly, the inhibition of C3 on host cell autophagy could significantly suppress the clearance of T. gondii by the IFN-γ-primed macrophage. Finally, we investigated the mechanism of the autophagy regulation of C3 that the effect of C3 on the macrophage-specific autophagy against T. gondii depends on mTOR. And, there is C3a but not C5a/C5aR involved in regulating macrophage xenophagy against T. gondii. Collectively, our findings suggest locally generated C3 regulates the clearance of T. gondii by Macrophage through the regulation of the noncanonical IFN-γ-dependent autophagy pathway, and paint a clearer picture in the regulation of autophagy by innate immune components.